Genomics of habitat choice and adaptive evolution in a deep-sea fish - Gaither, Michelle R.; Gkafas, Georgios A.; de Jong, Menno; Sarigol, Fatih; Neat, Francis; Regnier, Thomas; Moore, Daniel; Grӧcke, Darren R.; Hall, Neil; Liu, Xuan; Kenny, John; Lucaci, Anita; et al. (Nature Ecology and Evolution, 2018)
Intraspecific diversity promotes evolutionary change, and when partitioned among geographic regions or habitats can form the basis for speciation. Marine species live in an environment that can provide as much scope for diversification in the vertical as in the horizontal dimension. Understanding the relevant mechanisms will contribute significantly to our understanding of eco-evolutionary processes and effective biodiversity conservation. Here, we provide an annotated genome assembly for the deep-sea fish Coryphaenoides rupestris and re-sequencing data to show that differentiation at non-synonymous sites in functional loci distinguishes individuals living at different depths, independent of horizontal spatial distance. Our data indicate disruptive selection at these loci; however, we find no clear evidence for differentiation at neutral loci that may indicate assortative mating. We propose that individuals with distinct genotypes at relevant loci segregate by depth as they mature (supported by survey data), which may be associated with ecotype differentiation linked to distinct phenotypic requirements at different depths.
EPrint Processing Status: Full text deposited in DRO